The role of abnormal haemodynamics and cardiac troponin T in cardiogenesis - Pang, Kar Lai (2017)
The heart is the first functioning organ to develop during embryogenesis to maintain the growing embryo with oxygen and nutrients. However, cardiogenesis is a complex and highly coordinated biological process, and any perturbation to this process can result in detrimental defects to the heart. Haemodynamics is known to play an important role in cardiac growth and vasculature remodelling. Congenital heart defects (CHDs) accounts for 0.4-1.3% of all live birth, whereas cardiomyopathy accounts for 8-11% of cardiovascular disease diagnoses detected in utero. Although the heart defects and cardiomyopathies are known to be attributed by genetic mutations, most cases have unknown etiology. Hence, OFT-banding model was employed to alter the haemodynamic loading via pressure overloading. Upon alteration of haemodynamics, enlargement of the heart with a spectrum of cardiac anomalies were found (e.g ventricular septal defects, thickened epicardium and dysmorphic atrioventricular valves) upon morphological and stereological analysis. A study of global differential expression of OFT-banded hearts by RNA sequencing revealed a number of differentially expressed genes and they were associated with cardioprotection, metabolism, shear stress and valve development; further, a reduction of apoptosis was seen in these banded hearts as well. One of the cardiac phenotypes seen upon OFT-banding, the abnormal primordial atrioventricular valve, was further characterized to provide an insight how the atrioventricular valve is affected upon alteration of haemodynamics. Aberrant expressions of extracellular matrix (ECM) genes such as TBX20, Aggrecan and Periostin alongside with the shear stress responsive genes (KLF2 and EDN1) were found, and a decrease in apoptosis was seen. Moreover, dysregulation of ECM proteins such as fibrillin-2, type III collagen and tenascin were further demonstrated in more mature primordial AV leaflets at HH35, with a concomitant decrease of ECM cross-linking enzyme, transglutaminase-2. In addition, for many years sarcomeric proteins have been associated with a range of cardiomyopathies, but only in recent years they have been linked to congenital heart defects (CHDs). To date, cardiac troponin T (TNNT2) has been associated with cardiomyopathies but not with isolated CHDs. TNNT2 encodes for cTnT regulatory proteins of the thin filament of the sarcomere and is vital for muscle contraction and force generation within cardiomyocytes. To investigate a role of TNNT2 in the early developing heart, targeted manipulation of TNNT2 was performed in embryonic chick to reduce the protein levels of cTNT (protein product of TNNT2) in ovo via translational block. Abnormal atrial septal growth, reduced ventricular trabeculation and ventricular diverticula were found upon TNNT2 morpholino treatment. The abnormal phenotype observed in the TNNT2 morpholino-treated groups was potentially suggested by differential expression of shear stress responsive gene, NOS3 gene.